Hygrothermal Comfort in Single-Family Housing Projects in the City of Portoviejo - Toala Zambrano, Luiggy Andrés (2022)
The present investigation shows the results of the hygrothermal comfort analysis, in several single-family homes in the city of Portoviejo. As a general objective, the creation of thermal guidelines was established, which serve construction professionals as a project tool. To do it, evaluations were carried out, using typological files, applying the ASHRAE 55 sensitive scale, in addition to precise digital tools. Once the analysis was carried out, we got as results the ratings by means of the CBE thermal comfort software, the statistical data of the typological matrix applied in the living places, and the design of the thermal guidelines throughout the housing envelope (windows, walls, subfloor and deck). These procedures concluded in an important contribution to the thermal solution of these houses, in addition to the importance of applying bioclimatic techniques, suitable materials that provide thermal insulation and the correct orientation.